2018
DOI: 10.1039/c8ta01801d
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature fully recyclable carbon fibre reinforced phenolic composites through dynamic covalent boronic ester bonds

Abstract: By utilizing the alcoholysis nature of boronate bonds, the CF/PBNR composites can be fully recycled at room temperature in ethanol solvent without sacrificing the mechanical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(83 citation statements)
references
References 51 publications
0
83
0
Order By: Relevance
“…While most previous works on vitrimer composites are focused on their capability of recycling and self-healing [ 54 , 55 , 56 , 57 ], rapid reshaping to fix a new permanent/temporary shape (including to reshape the distribution of inclusions) is of great potential in many engineering applications.…”
Section: Applications Of Vitrimer-like Smps and Their Compositesmentioning
confidence: 99%
“…While most previous works on vitrimer composites are focused on their capability of recycling and self-healing [ 54 , 55 , 56 , 57 ], rapid reshaping to fix a new permanent/temporary shape (including to reshape the distribution of inclusions) is of great potential in many engineering applications.…”
Section: Applications Of Vitrimer-like Smps and Their Compositesmentioning
confidence: 99%
“…Jing et al introduced PBA as a cross-linking agent in novolac resin, which was used to produce a carbon fiberreinforced polymer composite. 51 Charged boronate esters are relatively stable when bound in aqueous solutions, particularly in alkaline aqueous solutions. Thus, charged boronate ester bonds have been extensively applied for self-healing in hydrogels, which mainly employ water as a solvent.…”
Section: Boronic Acid and Reversible Estersmentioning
confidence: 99%
“…Jing et al reported a study on the efficient recycling of carbon fiber-reinforced polymer (CFRP), which is widely used in largescale industrial applications. 51 By applying PBA to the novolac resin (NR) raw materials used in various fields, crosslinks by dynamic reversible boronate linkages were introduced (Fig. 8a).…”
Section: Potential Industrial Applications Merited By Mechanical Robustness and Reprocessabilitymentioning
confidence: 99%
“…Carbon fibre reinforced plastic (CFRP) composite has been widely used in automotive industries, wind energy industries and other engineering applications due to its unique combination of low-weight, high elasticity and strength and good corrosion resistance [ 1 , 2 , 3 ]. The excellent mechanical properties of carbon fibre reinforced thermoset composites and their increasing affordability means that industrial demand continues to grow rapidly [ 4 ].…”
Section: Introductionmentioning
confidence: 99%